Association Between Basic Environmental Sanitation and Diarrhea Incidence Among Children Under Five in Kamonji Health Center Area, Palu - Riri Suwahyuni Wahid; Juwita Rahayu; Kiki Sanjaya; Nur Hikmah Buchair; Hasanah Hasanah; Sendhy Krisnasari (Jurnal EduHealth, 2025)
Based on the 2024 World Health Organization (WHO) report, diarrheal disease affected approximately 1.7 billion children globally and remains a major contributor to mortality among those under five years old. This research investigated the association between basic sanitation conditions and diarrhea incidence among children under five in the Kamonji Health Center area, Palu City. A quantitative design with a cross-sectional approach was applied. The total population included 2,926 children under five, from which 100 participants were selected using the Slovin formula and stratified random sampling. Respondents were distributed across four sub-districts: Ujuna (31), Kamonji (28), Siranindi (19), and Baru (19). Statistical analysis using the Chi-Square test indicated p-values of 1.000 for clean water quantity, 0.000 for latrine ownership, 0.000 for waste bin availability, and 0.574 for wastewater drainage. The results demonstrated significant relationships between latrine ownership and waste bin availability with diarrhea occurrence, while no significant relationship was identified for clean water quantity and wastewater drainage. These findings suggest that environmental health programs should focus on improving household sanitation facilities and promoting routine health education to enhance community understanding of proper sanitation practices and diarrhea prevention strategies.